2012
DOI: 10.1017/s0033291712001006
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potential examination of facial affect processing in bipolar disorder and schizophrenia

Abstract: Background Patients with bipolar disorder exhibit consistent deficits in facial affect identification at both behavioral and neural levels. However, little is known about which stages of facial affect processing are dysfunctional. Methods Event-related potentials (ERPs), including amplitude and latency, were used to evaluate two stages of facial affect processing: N170 to examine structural encoding of facial features and N250 to examine decoding of facial features in 57 bipolar disorder patients, 30 schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 34 publications
(53 reference statements)
1
45
2
Order By: Relevance
“…This is consistent with previous studies showing delays in processing configural aspects of faces (Butler et al, 2008), increased reaction time in making social appraisals (Taylor et al, 2011), impaired early-stage processing of faces in electrophysiological studies (Turetsky et al, 2007; Wynn et al, 2013) that may be related to impaired structural encoding of faces (Turetsky et al, 2007), and possibly impaired time continuity in schizophrenia (Giersch et al, 2013). Thus, impairments in temporal processing also extend to the ability to make a first impression.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies showing delays in processing configural aspects of faces (Butler et al, 2008), increased reaction time in making social appraisals (Taylor et al, 2011), impaired early-stage processing of faces in electrophysiological studies (Turetsky et al, 2007; Wynn et al, 2013) that may be related to impaired structural encoding of faces (Turetsky et al, 2007), and possibly impaired time continuity in schizophrenia (Giersch et al, 2013). Thus, impairments in temporal processing also extend to the ability to make a first impression.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the laboratory setting and the measurement devices are factors that render the environment unnatural for these patients, masking some of the effects. Despite normal N170 and N250 amplitude and latency among the three groups in our study, previous research has found that patients with schizophrenia showed significantly longer latency compared to healthy controls [27]. These differences may be due to the small sample size of our study, or reflect the fact that the patients with schizophrenia in our study were very recently diagnosed and so are likely to be in the early stage of the disease.…”
Section: Discussioncontrasting
confidence: 71%
“…On the other hand, divergent patterns of neural activation on emotion tasks have primarily been isolated to areas showing higher activation in BD than SCZ in medial temporal lobe structures (e.g., hippocampus, parahippocampal gyrus, and mid-cingulate cortex) (Whalley et al, 2012). Electrophysiological studies also suggest that patients with SCZ and less so BD have deficits in structural encoding of faces, whereas both patient groups may show less efficient decoding of facial affect features (Wynn et al, 2013; Wynn et al, 2008). These neurophysiological findings may partly account for similarities between SCZ and BD-P in recognizing specific facial expressions (e.g., anger, neutral) but greater deficits for SCZ in judging other emotions (e.g., sadness, happiness).…”
Section: Discussionmentioning
confidence: 99%